Holmium doped yttria transparent ceramics for 2-μm solid state lasers - Wang, Jun (2019)
0.7 at.% Ho:Y2O3 transparent ceramics were fabricated by using vacuum sintering plus hot isostatic pressing (HIPing) process. Vacuum sintered at 1500 °C for 12 h followed by HIPing at 1450 °C for 4 h, the Ho:Y2O3 ceramics showed excellent in-line transmission and uniform grain size, with an average grain size of about 1 μm. The Ho:Y2O3 ceramics showed good thermal conductivity thanks to the identical effective ionic radius between Ho3+ and Y3+. For the first time, room temperature laser oscillation from Ho:Y2O3 transparent ceramics was demonstrated. The uncoated 0.7 at.% Ho:Y2O3 ceramic slabs were in-band pumped by a Tm:fiber laser at 1941 nm, and a maximum output power of 1.3 W at 2116.8 nm was achieved with a slope efficiency of 31.2%. It indicates that Ho:Y2O3 transparent ceramics could be excellent laser gain medias for 2 μm solid-state laser applications.